Social inequalities, sexual tourism and HIV in Cartagena, Colombia: an ethnographic study - M. C. Quevedo-Gómez; A. Krumeich; C. E. Abadía-Barrero; H. W. van den Borne (BMC Public Health, 2020)
Abstract Background Cartagena, Colombia’s main port on the Caribbean Coast, reported an HIV incidence of 7.5 per 100,000 inhabitants in 2007 with 90.0% transmission by heterosexual contact and 70 identified as women with a stable partner. Studies across Colombia illustrate that HIV infection relates to social inequalities; most people with HIV live in poverty and have minimal access to health care, education, and secure jobs. The purpose of this article is to analyse the relationship between social inequalities, sexual tourism and HIV infection in Cartagena, Colombia. Methods Data come from a five-year participatory ethnography of HIV in Cartagena in the period 2004–2009, in which 96 citizens (30 of whom were living with HIV) participated in different data collection phases. Techniques included participant observation, in-depth interviews and thematic life histories. Out of this material, we selected three life histories of two women and a man living with HIV that are representative of the ways in which participants expressed how social inequalities make it virtually impossible to engage in safe sex practices. Results At stake is the exchange of condomless sex for goods within the widespread sexual tourism networks that promote an idealisation of dark-skinned men and women as better sexual performers. Our results illustrate the complex interplay of social inequalities based on class, skin colour, gender and sexual orientation. Furthermore, they suggest a synergistic effect between poverty, racialization, and gender inequalities in the historical maintenance of social dynamics for a fruitful growth of a sexual tourism industry that in turn increases vulnerability to HIV infection. Conclusions Although the convergence of social inequalities has been thoroughly reported in the literature on social studies of HIV vulnerability; distinctive dynamics are occurring in Cartagena, including a clear link between the contemporary globalised sexual tourism industries and a racialised social structure - both having historical roots in the colonial past-.